Linking Inflation Differential Across Regions to Unemployment in the Philippines - Consing, Rafael Martin M; Lumba, Angelo Jose B; Alvarez, Julian Thomas B (Asian Journal of Economic Modelling, 2018)
We examine and econometrically test for the link between inflation differential across regions and unemployment in the Philippines from 2005 to 2017. Using optimal currency areas as a theoretical basis, this study sets up the Philippines as a currency union and regions as member countries which experience shocks idiosyncratically with the expectation that inflation differential across regions negatively correlates with national unemployment when wage flexibility acts as an adjustment mechanism. Using ordinary least squares estimation and the average of square differences in regional inflation from the mean as a measure for inflation differential across regions, we find that a unit increase in inflation differential across regions decreases the unemployment rate by 0.22 percentage points, indicating that wage flexibility acts as an adjustment mechanism against adverse idiosyncratic shocks in the Philippines. Interestingly, inflation is positively correlated with unemployment even when controlling for supply side shocks in the form of oil price inflation, suggesting that the Phillips curve was not present in the Philippines from 2005 to 2017. The study uses heteroscedasticity-and-autocorrelation-consistent standard errors and tests for unit roots and robustness to ensure the validity of its estimates.